Influence of shortest route approximation on relegating urban area’s transportation network priorities - Farid Morsidi,; Haldi Budiman, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Vehicle routing instances designed for a proficient distribution network strategizing at maximizing traversal coverage had been consistently investigated for resolving dominant logistics scheduling issues involving cost reduction characteristics aside from emulating optimal travel patterns for minimizing possible traveling ranges while maximizing resource allocations. The purpose of this research is to highlight the incorporation of shortest path routing heuristics for maximizing traversable nodes of a round trip distribution cycle, to stretch the qualities of sentient pathfinding capabilities from prominent intelligent graph traversal algorithm specimens to produce prudent output in terms of addressing cost optimality constraints. This greedy pathfinding algorithm is regarded as proactive for application in several known neighboring routing characteristics, including customer clustering aspects in vehicle routing and location-allocation instances for optimal resource allocation.